Neurological Patients during the Covid-19 Pandemic - Salles, Débora; Santino, Samara Ferreira; Malinverni, Andréa Cristina de Moraes; Stávale, João Norberto (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2022)
With the current pandemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), measures of social isolation were necessary, and this resulted in the interruption of several treatments. Regarding neuro-oncological patients, especially those with central nervous system (CNS) disorders, this interruption can cause serious damage or even compromise the success of the treatment in the future. It is essential that each case be evaluated separately to decide how to continue treatment during the pandemic, always considering the risk of SARS-CoV-2 infection and the benefits that the treatment will bring. The policy of not prescribing potentially toxic drugs, chemotherapy, and immunosuppressive therapies, as well as the use of techniques like stereotactic biopsy and telemedicine are important strategies at this time.
Keywords: coronavirus; neuro-oncology; treatment